2018
DOI: 10.18805/ijare.a-4793
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and phylogenetic analysis of NBS-LRR genes in wild relatives of eggplant (Solanum melongena L

Abstract: Eggplantor brinjal (Solanum melongena L.), is highly susceptible to various soil-borne diseases. The extensive use of chemical fungicides to combat these diseases can be minimized by identification of resistance gene analogs (RGAs) in wild species of cultivated plants.In the present study, degenerate PCR primers for the conserved regions ofnucleotide binding site-leucine rich repeat (NBS-LRR) were used to amplify RGAs from wild relatives of eggplant (Black nightshade (Solanum nigrum), Indian nightshade (Solanu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Similarly Prakashkumar Unnikrishnan et al, (2014) [27] reported that that the essential oil extracted from the leaves and stem of E. triplinerve is the source of thymohydroquinone dimethyl ether which is found to have significant antimicrobial effect. Sona Dev et al, (2018) [31] reported that Silver nanoparticles (AgNPs) which are bio synthesized from the leaf extracts of E. triplinerve showed excellent antibacterial activity. Akhtar Nahid et al, (2017) [32] interpreted the antimicrobial activity of E. prostrata as the plant extract showed the ability to inhibit the growth of both gram positive and gram negative bacterial strains.…”
Section: In Vitro Antibacterial Activitymentioning
confidence: 99%
“…Similarly Prakashkumar Unnikrishnan et al, (2014) [27] reported that that the essential oil extracted from the leaves and stem of E. triplinerve is the source of thymohydroquinone dimethyl ether which is found to have significant antimicrobial effect. Sona Dev et al, (2018) [31] reported that Silver nanoparticles (AgNPs) which are bio synthesized from the leaf extracts of E. triplinerve showed excellent antibacterial activity. Akhtar Nahid et al, (2017) [32] interpreted the antimicrobial activity of E. prostrata as the plant extract showed the ability to inhibit the growth of both gram positive and gram negative bacterial strains.…”
Section: In Vitro Antibacterial Activitymentioning
confidence: 99%
“…It is interesting to note that a large number of R genes, which share several conserved domains i.e., leucine-rich repeat (LRR), nucleotidebinding sites (NBS) and protein kinase domain, implicate resistance against a large spectrum of pathogens. These conserved domains have been found in genes isolated from genomes of several plant species i.e., tomato, eggplant and legume crops (Wei et al, 2016;Dev et al, 2018;Tirnaz et al, 2020). Recently, we developed a new type of marker, ISSRanchored resistance gene analog (ISSR-RGA), using ISSR primers combined with gene-targeted RGA primers to detect the SSRs dispersed at multiple loci in proximity to RGAs throughout the mungbean genome and found that the ISSR-RGA markers are more effective than ISSRs for successfully identifying the gene conferring PM resistance in the 'CN72 × V4718' cross (Poolsawat et al, 2017).…”
Section: Association Of Issr and Issr-rga Markers With Powdery Mildew...mentioning
confidence: 99%
“…The SERK3 was amplified in all the three stages of calli showing its importance in SE as it is required for the formation and maturation of embryos (Figure 4a, b). If the Phylogenetic analyses of the predicted sequences is performed, then that may be helpful to analyze or characterize the genetic role for accurate functioning of the gene for regeneration potential in the local varieties as has been observed by Dev et al (2018) in Eggplant.…”
Section: Pcr For Serk3 Gene Identification In Callimentioning
confidence: 99%